The impact of the cytochrome CYP2C9*2 and *3 polymorphisms in the South African Caucasian population on warfarin therapy protocols - Bester, Megan J. (University of Pretoria, 2013)
Dissertation (MSc (Chemical Pathology))--University of Pretoria, 2005.